Effect of Sizing Agents on Surface Properties of T800 Grade CF and Thermal Aging Time on Mechanical Properties of T800 Grade CF/Epoxy Composites - Tian Yang (Hindawi Limited, 2021)
This paper investigates the effect of sizing agent molecular weight on carbon fiber (CF) surface properties and the effect of thermal aging time on mechanical properties of CF/epoxy composites. The surface properties of three CCF800 CF samples with varying sizing agent molecular weight were characterized by surface morphology, surface roughness, chemical functional groups, and element composition. The results showed that the sample with low molecular weight exhibited low roughness and high proportion of activated carbon atoms. The flexural strength, flexural modulus, and interlaminar shear strength of CCF800/5228 composites were measured at 25°C and 150°C by thermal ageing time 0, 100 h, 250 h, 500 h, and 1000 h. The results showed that the thermal aging time up to 1000 h had little effect on the flexural modulus, and the interlaminar shear performance at 150°C showed a trend of increasing at the beginning and then decreasing.